2022
DOI: 10.1681/asn.2022030373
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Recognition, Monitoring, and Management of CKD in Health Care: An Observational Cohort Study

Abstract: IntroductionReported sex differences in the etiology, population prevalence, progression rates, and health outcomes of people with CKD may be explained by differences in health care.MethodsWe evaluated sex as the variable of interest in a health care–based study of adults (n=227,847) with at least one outpatient eGFR<60 ml/min per 1.73 m2 measurement denoting probable CKD in Stockholm from 2009 to 2017. We calculated the odds ratios for diagnosis of CKD and provision of RASi and statins at inclusion, and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
2
30
0
1
Order By: Relevance
“…Although these findings were observed in a Swedish population, a previous review by Carrero et al 7 highlights numerous disparities in processes and outcomes of care in other countries. The findings of Swartling et al 2 were observed despite reporting of eGFR by clinical laboratories in the later years of the study. Larger disparities might be expected if clinical laboratories report only serum creatinine, which is lower in women than in men with the same measured GFR.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Although these findings were observed in a Swedish population, a previous review by Carrero et al 7 highlights numerous disparities in processes and outcomes of care in other countries. The findings of Swartling et al 2 were observed despite reporting of eGFR by clinical laboratories in the later years of the study. Larger disparities might be expected if clinical laboratories report only serum creatinine, which is lower in women than in men with the same measured GFR.…”
mentioning
confidence: 69%
“…Currently, kidney biopsy is the only clinical tool to assess the extent of tubulointerstitial injury, because GFR correlates poorly with severity of nephrosclerosis. 2 Therefore, identification of novel biomarkers of kidney health, such as markers of tubular dysfunction or injury measurable in urine or blood specimens, has the potential to revolutionize the approach to diagnosis and management of CKD.…”
Section: Author Contributionsmentioning
confidence: 99%
See 3 more Smart Citations